The rhetoric of patriotism and networks of scientific information in Central America, c. 1790-1810 - Brockmann, Sophie (Cuadernos de Historia Moderna, 2012)
This article explores the relationship between scientific endeavours and the rhetoric of creole patriotism in the Spanish colony in Central America, the Captaincy-General of Guatemala towards the end of the colonial period. It focuses specifically on the statements made by the patriotic newspaper Gazeta de Guatemala about the trustworthiness of expert scientific knowledge and the applicability of foreign knowledge to Guatemalan circumstances. Guatemalan scholars participated in networks for the exchange of scientific information within the Spanish empire, but also built up their own network of contacts within the colony, the Caribbean, and even North America, and could pit these sources of knowledge against each other. Although feelings of creole patriotism were not translated into a political independence movement until the 1820s, it is still possible to observe a patriotic slant in arguments made about science and the reliability of scientific sources.